Implementation of the project for strengthening the profile of pancasila students in the primary school level mobilization school program in soppeng regency - Hamzah, Rahma Ashari (Universitas Nusantara PGRI Kediri, 2024)
The aim of this research is to see how the project to strengthen the profile of Pancasila students is implemented which seeks to improve skills in implementing the project to strengthen the profile of Pancasila students, especially in the Third Year 1st Generation Mobilization School Program at elementary school level in Soppeng Regency. The research method used is a qualitative descriptive method, namely research carried out to describe activities, events, phenomena, perceptions of people individually and in groups. An important finding in this research is based on the results that all parties involved in the project activities to strengthen the profile of Pancasila students are very enthusiastic and enthusiastic in implementing the project to strengthen the profile of Pancasila students in their respective educational units. Many parties were involved in the project such as the principal, school supervisor, class teachers, subject teachers, students and outside parties were also involved such as parents of students and the community as well as groups who were experts in their fields such as local traditional leaders, community health center employees, and so on. so that it can strengthen the character of students according to the Pancasila student profile.